Late Weichselian Ice Sheet in Eurasia and Greenland. - Svendsen, John Inge; Astakhov, Valery I; Bolshiyanov, Dimitry Yu; Demidov, Igor; Dowdeswell, Julian A; Gataullin, Valery; Hjort, Christian; Hubberten, Hans-Wolfgang; Larsen, Eiliv; Mangerud, Jan; Melles, Martin; Möller, Per; et al. (PANGAEA, 1999)
Based on field investigations in northern Russia and interpretation of offshore seismic data, we have made a preliminary reconstruction of the maximum ice-sheet extent in the Barents and Kara Sea region during the Early/Middle Weichselian and the Late Weichselian. Our investigations indicate that the Barents and Kara ice sheets attained their maximum Weichselian positions in northern Russia prior to 50 000 yr BP, whereas the northeastern flank of the Scandinavian Ice Sheet advanced to a maximum position shortly after 17000 calendar years ago. During the Late Weichselian (25 000-10000 yr BP), much of the Russian Arctic remained ice-free. According to our reconstruction, the extent of the ice sheets in the Barents and Kara Sea region during the Late Weichselian glacial maximum was less than half that of the maximum model which, up to now, has been widely used as a boundary condition for testing and refining General Circulation Models (GCMs). Preliminary numerical-modelling experiments predict Late Weichselian ice sheets which are larger than the ice extent implied for the Kara Sea region from dated geological evidence, suggesting very low precipitation.
Reconstructed glaciation limits in Eurasia (digitized from map Fig.1)
Keywords: IceExtArkhipov1986; IceExtSvendsen1999; Quaternary Environment of the Eurasian North; QUEEN; QUEENModels; RECON; Reconstructed data